Macroscopic Supramolecular Assembly to Fabricate 3D Ordered Structures: Towards Potential Tissue Scaffolds with Targeted Modification. (15th October 2015) - Cheng, Mengjiao; Wang, Yue; Yu, Lingling; Su, Haijia; Han, Weidong; Lin, Zaifu; Li, Jianshu; Hao, Haojie; Tong, Chuan; Li, Xiaolei; Shi, Feng
Abstract : 3D ordered structures beyond microscale with targeted modification are catching increasing attention due to its application as tissue scaffolds. Especially scaffolds with necessary growth factors at designated locations are meaningful for induced cell differentiation and tissue formation. However, few fabrication methods can address the challenge of introducing bioactive species to the interior targeted places during the preparation process. Herein, for the first time macroscopic supramolecular assembly is applied to obtain such 3D ordered structures and established a proof‐of‐concept idea of complex scaffold with targeted modification. Taking strip‐like polydimethylsilicon building block as a model system, microscaled multilayered structures have been fabricated with parallel aligned building blocks in each layer. The morphology can be adjusted in a flexible way by tuning the number of layer, the space between two adjacent building blocks, and the position and orientation of each PDMS. The as‐prepared 3D structures are demonstrated biocompatible and potential as scaffolds for 3D cell culture. Moreover, bioactive species can be in situ incorporated into designated locations within the 3D structure precisely. In this way, a novel strategy is provided to address the current challenges in fabricating complex 3D tissue scaffolds with localized protein for future induced cell differentiation. Abstract : For the first time, macroscopic supramolecular assembly is applied to fabricate periodically stacked 3D ordered structures with biocompatibility and potential as tissue scaffolds. Special building blocks with bioactive species are introduced in situ to designated locations within the 3D structure, which provides a proof‐of‐concept idea of fabricating 3D scaffolds with targeted modification of growth factors for directed cell differentiation.